Rebuilding with a heart: architecture roles in post-disaster psychosocial interventions - Dy, Gloryrose Alcoran; Naces, Maria Lovella Parcon (Journal of Architecture and Urbanism, 2016)
The presented paper focuses on the role of architecture in post-disaster humanitarian efforts particularly on the return to normalcy and sustainable recovery. Two major approaches were introduce, ‘Architecture of empowerment’ and ‘Strengths-based approach’ to analyze two cases of post disaster rebuilding projects employed in Batug, Leyte Philippines after super-typhoon Haiyan. The objective of the paper was to formulate a framework for post-disaster humanitarian efforts in order to achieve sustainable recovery. Another objective was to look at the interrelationship of the humanitarian architecture and psychosocial intervention or the journey to normalcy. Key Informant Interviews with locals, observers and participants of the shelter project, were used to gather information for both projects. Qualitative analysis and descriptive method were used for the interpretation the gathered data. In the end, a framework was formulated which points out that the integration with the roles of humanitarian architecture ( provider, supporter and catalyst) with strength-based approaches in post-disaster efforts factors of resources, competencies and sustainable recovery and the interplay of all these factors are the vital elements in order to have successful rebuilding projects after disasters.